Frequency of chemotherapy Induced Gait Deviations in Breast Cancer Female Survivors - Fatima Zahid; Hufsa Tariq; Hafiz Muhammad Asim (Journal Riphah College of Rehabilitation Sciences)
Background: Prolonged chemotherapy treatment in breast cancer patients can lead to the development of chemotherapy-induced peripheral neuropathy (CIPN). CIPN is a common adverse effect characterized by symptoms such as gait and balance impairments, as well as weakness in the lower extremities. These symptoms can significantly impact functional abilities and increase the risk of falls among patients. Importantly, these effects may persist even after completion of chemotherapy treatment, leading to long-term challenges in mobility and balance.